Localized discoid lupus erythematosus. - Pisani, V. (European Journal of Pediatric Dermatology, 2013)
A 17-year-old boy in good health was first observed due to the presence from 6 months of persistent skin lesions on the face and scalp. The personal and family history was negative for autoimmune diseases, nor were referred joint pain or peripheral circulation disorders. His lesions, started in the spring, worsened during summer. The physical examination showed six erythematous lesions with clear-cut borders, 0.5-2 cm in diameter on the front, left cheek and bridge of the nose (Fig. 1) and a 3 cm in size lesion on the right parietal region (Fig. 2). The nasal and parietal lesions showed slight hyperkeratosis adherent to the background erythema. The laboratory examinations were negative or within normal limits except for antinuclear antibodies of homogeneous type with 1:160 titre. The histological examination (Fig. 3) showed vacuolar degeneration of the epidermal basal layer, follicular keratosis and perifollicular lymphocytic infiltrate, leading to the diagnosis of localized discoid lupus erythematosus.